A study on the factors affecting underpricing of venture capital and non-venture capital-backed IPOs in the Philippines - Canlas, Marion Angelique A. (Animo Repository, 2017)
This paper studies the occurence of underpricing in the Philippine Stock Exchange (PSE) and the factors that affect underpricing in venture and non-venture capital-backed companies. Independent variables such as, age of the firm from time of incorporation to the year of IPO, timing of the offer, size of the offer, size of the firm, and market share of the lead underwriter were used to study its relationship with underpricing. The researchers gathered information on Philippine IPOs performed from 2006 to 2016 and ran separate multiple linear regressions for the venture capital-backed companies, non-venture capital-backed companies, and a combination of both types of companies. The study concluded that underpricing occur in the PSE. Furthermore, the regression model for the venture capital-backed companies found that age of the firm, offer size, and market share of the lead underwriter is negatively related to underpricing, while timing of the offer is positively related to underpricing. For the regression model for the non-venture capital-backed companies, age of firm, offer size, and timing of the offer were found to have a positive relationship with underpricing. The results for the regression model of the combined sample was consistent with the regression results of the non-venture capital-backed companies' regression model. Timing of the offer was found to have a significant effect in the non-venture capital-backed and combination regression models. Size of the offer was also found to have a significant effect in the non-venture capital-backed regression model.